Verba Pasif dalam Cerpen Pelajaran Mengarang Karya Seno Gumira Ajidarma - Marliah, Elva; Sari, Niken Rahma; Karunia, Dona Aji (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze passive verb contained in a short story entitled The Lesson Making Seno Gumira Ajidarma. The analysis was carried out in a short story entitled Lesson Making up. The method used by the researcher is a qualitative descriptive method, using several techniques in analyzing, namely, first, the technique of read which is to read intensively in short stories. Second, recording techniques that realize them are by recording passive forms and classifying passive forms based on lexical markers. Third, the data analysis technique whose realization is in how data in this study is analyzed using passive-blown theories of experts. The results show that passive verb in the short story of Seno Gumira Ajidarma Lesson is 3 types of passive verb with a number of 21 words, namely di-'s passive verb there are 9 words, ter-'s passive verb there are 10 words, and passive verbs there are 2 words. Then in this study describes the verb of morphological markers contained in passive verb, with this type of passive verb and passive verb intrasitif and its role in explaining activities in a sentence.